Blind detection of interlever parameters for block and convolutional coded sequences - Liu, Xuezhe. (2012)
Channel encoding is implemented in most digital communications to combat transmission errors, which is achieved by adding additional parity check bits to the data stream. However, channel encoder will not be able to handle the effects of fading or burst errors. As a result, an interleaver is needed to permute the data stream in order to separate the burst errors and to reduce the effects of fading. This project aims to estimate the interleaver parameters in a non-cooperative context. As in this situation, only the intercepted data is known. Blind detection of the interleaver period and the code rate becomes crucial.